Clash of Champions Gamification and Mathematics Learning Motivation among Elementary School Students - Dina Awwalya Fauziyah; Heny Kusmawati (Institut Agama Islam Negeri Palangka Raya, 2026)
This study explores the use of Ruangguru Clash of Champions gamification in shaping fourth-grade students’ mathematics learning motivation at Kauman Pati Islamic Elementary School. The study responds to the need for more engaging mathematics learning by examining how a popular edutainment-based platform is pedagogically integrated into classroom practice. A descriptive qualitative design was employed, involving the school principal, one fourth-grade teacher, fourth-grade students, and selected student interviewees as research informants. Data were collected through classroom observation, semi-structured interviews, and documentation, and were analyzed using the interactive model of data condensation, data display, and conclusion drawing/verification. The findings show that Clash of Champions shaped students’ motivation through school support, teacher mediation, competitive features, immediate feedback, and classroom regulation. Features such as Math Mayhem, points, rankings, leaderboards, and time-limited challenges encouraged students’ enthusiasm, participation, focus, quick thinking, and achievement orientation. However, the findings also revealed emotional and technical tensions, including anxiety, fear of making mistakes, time pressure, limited Smart TV availability, internet dependence, and classroom time management issues. This study contributes to gamified mathematics learning literature by conceptualizing Clash of Champions as a teacher-mediated pedagogical ecosystem rather than a stand-alone digital intervention. The study implies that gamification can support elementary mathematics learning when it is accompanied by teacher guidance, classroom agreements, feedback-based reflection, emotional support, and adequate digital infrastructure.